2015
DOI: 10.3945/ajcn.114.091934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initiating enteral protein feeding on whole-body protein turnover in critically ill patients

Abstract: Whole-body protein turnover and the contribution of dietary protein can be quantified in critically ill patients by using intravenous and enteral stable-isotope Phe tracers. The whole-body protein balance improved during early hypocaloric-hyponitrogenous enteral protein feeding in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 35 publications
2
47
0
1
Order By: Relevance
“…Therefore, we would advocate a more conservative attitude in general recommendations pending creation of more solid knowledge. We see no rationale for a higher protein intake than the ESPEN guidelines recommendation, even if whole body protein balance is more positive as our own studies demonstrate [11, 1315], unless clinical relevant advantages can be demonstrated in randomized studies. In parallel, we need to better identify the possible risks involved with a high-protein intake on the level of the individual patient.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, we would advocate a more conservative attitude in general recommendations pending creation of more solid knowledge. We see no rationale for a higher protein intake than the ESPEN guidelines recommendation, even if whole body protein balance is more positive as our own studies demonstrate [11, 1315], unless clinical relevant advantages can be demonstrated in randomized studies. In parallel, we need to better identify the possible risks involved with a high-protein intake on the level of the individual patient.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, this limited knowledge of the regulation of quantities of individual protein as well as mixed protein in tissues or in the whole body make it difficult to decide on what grounds recommendations of protein intake should rest. At a whole body level, and as a group, critically ill patients utilize extra nutritional proteins to build body protein and they do not oxidize these [11, 1315], but due to the black box principle it is not clear which protein are synthesized and whether they benefit the patient.…”
Section: Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended procedure is to measure the enteral uptake in parallel to the measurements of protein turnover by tracer techniques, by assessing the enteral uptake by an additional tracer. This is illustrated by a comparison between healthy volunteers and intensive care unit (ICU) patients, who exhibit very different levels of first‐pass elimination 5 . Furthermore, it is usually not possible to have an amino acid tracer in your dietary proteins digested.…”
Section: Basic Physiology Of Feedingmentioning
confidence: 99%